2013
DOI: 10.1098/rsbl.2013.0838
|View full text |Cite
|
Sign up to set email alerts
|

Rates of transposition in Escherichia coli

Abstract: The evolutionary role of transposable elements (TEs) is still highly controversial. Two key parameters, the transposition rate (u and w, for replicative and non-replicative transposition) and the excision rate (e) are fundamental to understanding their evolution and maintenance in populations. We have estimated u, w and e for six families of TEs (including eight members: IS1, IS2, IS3, IS4, IS5, IS30, IS150 and IS186) in Escherichia coli, using a mutation accumulation (MA) experiment. In this experiment, mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…Although PMPs are much shorter sequences than ISs, if we take 10 26 as a conservative estimate of a possible HGT rate for PMPs, this would imply that the duplication and loss rates for PMPs would be of order 10 25 . These values would be consistent with recent direct estimates of IS replicative transposition rates of 10 25 for six transposable elements in Escherichea coli (Sousa et al 2013). Sousa et al also found that for at least two of these ISs (IS2 and IS5), the excision rate was almost as large as the duplication rate.…”
Section: Discussionsupporting
confidence: 80%
“…Although PMPs are much shorter sequences than ISs, if we take 10 26 as a conservative estimate of a possible HGT rate for PMPs, this would imply that the duplication and loss rates for PMPs would be of order 10 25 . These values would be consistent with recent direct estimates of IS replicative transposition rates of 10 25 for six transposable elements in Escherichea coli (Sousa et al 2013). Sousa et al also found that for at least two of these ISs (IS2 and IS5), the excision rate was almost as large as the duplication rate.…”
Section: Discussionsupporting
confidence: 80%
“…coli [17]. In fact, IS insertions occurred in 6 out of the 7 targets of adaptation identified through parallelism.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicated that transposition frequency can be perturbed by growth temperatures (McClintock, 1984; Ohtsubo et al, 2005; Sousa et al, 2013). To tune the transposition rate, experiments were carried out with cells cultured at a lower 34 °C temperature, which was shown to slow down crosstalk triggered mutation of this circuit (Figure S4B).…”
Section: Resultsmentioning
confidence: 99%